Sistem Informasi Peramalan Stok Barang di Toko Al Umm Menggunakan Metode Single Moving Average - Moch Khoirul Muna Muna; Irfan Pratama (Journal of Information System and Artificial Intelligence, 2023)
Al Umm store is a wholesale and retail store for Muslim clothing that provides various kinds of worship tools such as sarongs, mukena, caps and blankets. With the various kinds of goods available at the Al Umm store, it is difficult for the shop owner to know the stock of goods available in his shop with certainty. To record the stock of these goods, the shop owner still records it manually so the owner does not know for sure how much stock is still available in the store. Therefore, the authors took the initiative to build an application to forecast the stock of goods at the Al-Umm Store using the PHP programming language with the CodeIgniter 3 framework. The author also uses a single moving average forecasting method where this forecasting method is used to determine the amount or number of stock items which needs to be supplied at the Al-Umm shop.